Possible role of grape fruit in controlling hyperglycemia and associated complications: Better glycemic control in healthy subjects through fruits fibers as compared to fruit juices (Bangladesh Journal of Medical Science, 2020)
Background: Diabetes is regarded as a chronic disorder, which is globally spreading at an alarming rate and individuals are being pushed down by the burden of diabetes. Different measures and control programs have been conducted for awareness of this disaster endocrine disease as its associated complications.Objective: Current study has been conducted to evaluate the hypothesis that whole fruits provide better glycemic control than fruit juices.Materials & Methods: The study includes two groups of healthy volunteers, one group was on whole fruits while another group was supplied with fruit juices of same fruits and fasting blood sugar and random blood sugar were monitored.Results: Results revealed that whole grapefruit and orange fruit play effective role in maintaining random blood sugar levels in comparison to juices. Further suggested that dietary fibers are not only effective in regulating blood sugar, but also influence on blood pressure and pulse rate.Conclusion: Based on above findings, it has been concluded that type 2 diabetes patients can achieve better glycemic control by dietary fibers rather than juices, and it may be helpful in controlling diabetes related complication such as high blood pressure.Bangladesh Journal of Medical Science Vol.19(3) 2020 p.480-485